PENGARUH PEMBERIAN BERBAGAI KULIT JERUK SEBAGAI REPELENSI KUTU BERAS (Sitophilus oryzae L.) DAN SUMBANGSIHNYA PADA MATERI HAMA DAN PENYAKIT PADA TANAMAN DIKELAS VIII - Desma Susanti; Choirun Niswah; Riri N Sunarti (Bioilmi: Jurnal Pendidikan, 2018)
This study entitled the effect of giving various orange peels as a repelence of rice lice (Sitophillusoryzae L.) and its contribution to pest and disease material in plants in class VIII. This study aims todetermine the effectiveness of various orange peels as a repelence of what type of rice lice andorange skin is most effectively used as a repelence of rice lice. The type of research used in thisstudy is quantitative descriptive research (where the data collection process uses statistical analysis)and the experimental method. The data obtained were analyzed statistically using Analysis ofVarience (ANOVA). Analysis of the variance of the treatment effects for a complete randomizeddesign (CRD) was carried out according to the F test. Based on the results of the research, eachtreatment was significantly different from the control. The highest percentage of rejection wasfound in the treatment of lime peel, which amounted to 56.25 at 76 hours and the lowest percentagewas found in the treatment of sunkist orange peel ie 27.5 at 76 hours. Hypothesis testing results forF count treatment (19> 1.79) and F count Factor A (40> 2.99) and F count on Factor B (102> 3.20),this states that slices of various orange peels (Citrus sp.) very significant effect to reject riceinfestation (Sitophillus oryzae L.), so that it is stated that H1 is accepted and H0 is rejected. Thus itcan be concluded that various citrus coolies are effective as repelensi rice mites (Sitophillus oryzaeL.).